PERAN GURU DALAM MEMBENTUK KARAKTER SISWA MELALUI PEMBELAJARAN KESANTUNAN BERBAHASA DI MEDIA SOSIAL - Yeni Rostikawati; Eli Syarifah; Woro Wuryani (Abdimas Siliwangi, 2020)
The role of the teacher in the world of education as a role model in which all his behavior and speech will be an example for his students. The role of teachers in the world of modern education is increasingly complex, not only as mere teachers and academic educators, but also educators of the character, morals, and culture of their students. The learning of politeness in the language is very important because indirectly the way a person speaks will reflect the character and nature of a person indirectly. Likewise for students as students who are close to politeness should be able to reflect the use of polite language. In this modern era teachers and students, even all groups are familiar with the name of social media as a means of delivering information and communicating. The language used on social media is most unethical and is far from what is called politeness in language. This is where the role of the teacher gives direction to students how to use this media wisely because it can be read by many people. This service uses a qualitative descriptive approach. Researchers will note in detail everything that can be investigated empirically With qualitative descriptive methods researchers hope to provide a change in politeness in language on social media.